Investigating the Effect of Concept Mapping in Learning Ethics in Accounting - Somayyeh Ghaffari; Ali Khozein (International Journal of Ethics and Society, 2022)
Background: The role, duty and responsibility of professional accountants towards the society, capital owners and other interested parties requires that they observe the general principles of good ethics in all aspects and adhere to the coded and consistent professional conduct. Therefore, the main goal of this research is to find a suitable method for meaningful (long-term) learning of ethics concepts in accounting. Method: This research was applied and semi-experimental and was carried out in a quasi-experimental manner. The statistical population was accounting master students, 50 of whom were selected by in access sampling and randomly divided into two experimental and control groups. The instrument was accounting ethics questionnaire and finally the data were analyzed by covariance method. Results: In this research, traditional teaching methods were compared with alternative methods (use of conceptual diagrams) by comparing the learning rate of two groups of accounting students. The findings of the research indicated that the average scores of the students of the experimental group (who were trained using conceptual diagrams) were significantly higher than the control group (who were trained using the traditional method). Conclusion: Nowadays, in many cases, traditional teaching methods are not able to understand the complex topics of ethics, and therefore students try to learn these topics like parrots. Conceptualization allows a person to communicate between different aspects of moral issues and to understand the relationship between ideas and constituent parts of thoughts. Therefore, using the conceptual diagram prepared by the lecturer or relevant experts in ethics education can increase the quality and quantity of participation in learning among students.